The association between peri‐operative acute risk change (ARC) and long‐term survival after cardiac surgery. (13th July 2017) - Coulson, T. G.; Bailey, M.; Reid, C. M.; Tran, L.; Mullany, D. V.; Smith, J. A.; Pilcher, D.
Summary: Acute risk change has been described as the difference in calculated mortality risk between the pre‐operative and postoperative periods of cardiac surgery. We aimed to assess whether this was associated with long‐term survival after cardiac surgery. We retrospectively analysed 22, 570 cardiac surgical patients, with minimum and maximum follow‐up of 1.0 and 6.7 years. Acute risk change was calculated as the arithmetic difference between pre‐ and postoperative mortality risk. 'Rising risk' represented an increase in risk from pre‐ to postoperative phase. The primary outcome was one‐year mortality. Secondary outcomes included mortality at 3 and 5 years and time to death. Univariable and multivariable analyses were undertaken to examine the relationship between acute risk change and outcomes. Rising risk was associated with higher mortality (5.6% vs. 3.5%, p < 0.001). After adjusting for baseline risk, rising risk was independently associated with increased 1‐year mortality (OR 2.6, 95%CI 2.2–3.0, p < 0.001). The association of rising risk with long‐term survival was greatest in patients with highest baseline risk. Cox regression confirmed rising risk was associated with shorter time to death (HR 1.86, 1.68–2.05, p < 0.001). Acute risk change may represent peri‐operative clinical events in combination with unmeasured patient risk and noise. Measuring risk change could potentially identify patterns of events that may be amenable to investigation and intervention. Further work with case review, and risk scoring with shared variables, may identify mechanisms, including the interaction between miscalibration of risk and true differences in peri‐operative care.